The attitude of Malaysian Indian plantation community as portrayed in selected Malaysian Tamil novels - Govindasamy Kolendai (Tanjong Malim, 2021)
The attitude of Malaysian Indian plantation community as portrayed in selected Malaysian Tamil novels by Govindasamy Kolendai